Living in Pasteur's Quadrant: How Conversational Duets Spark Language at Home and in the Community. Issue 4 (19th May 2018) - Hirsh-Pasek, Kathy; Alper, Rebecca M.; Golinkoff, Roberta Michnick
ABSTRACT: In 1995 scientists, educators, and policymakers were startled by the claim that low-income children in the United States heard 30 million fewer words than their middle-income peers. Because language is the single best predictor of later academic readiness, this gap can have consequences for children in school and beyond. Language researchers know much about the types of interactions that foster a strong foundation in language learning and about the kinds of interactions that can narrow the disparities. This article reviews the growing consensus in the field about how to reduce language gaps and challenges scientists to put the latest research on early language in the hands of parents and teachers who work with children every day. Our work connects the lab, the home, and the community and demonstrates a synergy between basic and applied science noted in the classic, Pasteur's Quadrant.